Treating the Different Phenotypes of Behçet's Syndrome - Bettiol, Alessandra; Hatemi, Gulen; Vannozzi, Lorenzo; Barilaro, Alessandro; Prisco, Domenico; Emmi, Giacomo (Frontiers in Immunology, 2019)
Behçet’s syndrome (BS) is a multisystemic vasculitis, characterised by different clinical involvements, including mucocutaneous, ocular, vascular, neurological and gastrointestinal manifestations. Based on this heterogeneity, BS can be hardly considered as a single clinical entity. Growing evidence supports that, within BS, different phenotypes, characterised by clusters of co-existing involvements, can be distinguished. Namely, three major BS phenotypes have been reported: a) the mucocutaneous and articular phenotype; b) the extra-parenchymal neurological and peripheral vascular phenotype; c) the parenchymal neurological and ocular phenotype. To date, guidelines for the management of BS have been focused on the pharmacological treatment of each specific BS manifestation. However, tailoring the therapeutic strategies on patient’s specific phenotype, rather than on single disease manifestation, could represent a valid strategy for a holistic, multisystemic approach to BS. In the present literature review, we summarize current evidence on the pharmacological treatments for the first, second and third line treatment of the major BS phenotypes.